TEACHER PROFESSIONALISM DEVELOPMENT STRATEGY TO IMPROVE LEARNING QUALITY AT MADRASAH ALIYAH NURUL JADID - Shulhani, Rahmat; Abdillah, Ikhwan; Pradani, Rizki Febri Eka (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Education at the Nurul Jadid Islamic Senior High School plays an role important in forming a superior generation in knowledge and religion. Teacher professionalism is the key to success in creating effective and innovative learning. Research This aims to identify development strategies for teacher professionalism and factor supporters and inhibitors. The methods used are approach qualitative descriptive, with data collection through interviews, observations, documentation, and questionnaires. Research results show that various strategies, such as training based on needs, academic supervision, and formation of community learning, have been applied to increase teacher competency. Support from madrasah leadership and culture Work cooperation among teachers becomes a factor Supporter main. However, the challenges like limitations time, facilities technology, and resistance to change Still become obstacles. Impact positive from teacher professionalism is visible in improvement involvement students and results learn more good. Technology integration in learning also becomes aspect crucial in facing challenges in education in the 21st century. Research This recommends improvement to support more facilities and training programs flexible for overcoming existing obstacles. It is hoped that efforts to develop teacher professionalism can continue so that the Nurul Jadid Islamic Senior High School can print competent and moral graduates.